A study of nineteenth century inheritance practices in the island of Sao Jorge (Azores archipelago) - Matos, P. T. de; Ana Mafalda Lopes (Rural History Conference 2023, 2023)
This chapter will analyze the transmission of property among widows in the parish of Ribeira Seca in the Azores, a Portuguese archipelago in the North Atlantic, in the 19thcentury. Through sources such as probate inventories, last wills, notarial records and lists of population we intend to understand (melhor contribuir para o conhecimento)how they used their property and wealth, analyzing what type of property and assets they possessed, its value and to whom they transmitted it.